An Empirical Study on Green Products and Green Marketing - Zaid, Ebrahim Sulaiman Ebrahim Hassan; Ravi, Dr.A. (The journal of contemporary issues in business and government, 2022)
Green or Environmental Marketing consists of all activities designed to generate and facilitate any exchanges intended to satisfy human needs, such that satisfaction of these needs and wants occur, with minimal detrimental impact on the natural environment. Primary data was collected by means of preparing a questionnaire and getting it filled by a large sample space. These questionnaires helped in drawing conclusions about the case. Secondary data was gathered from the books, internet sites, articles and journals on green marketing. With the help of the primary and secondary data so collected, along with the various statistical tools, an analysis will be performed. These tools provided a water tight conclusion for the case so framed. A questionnaire was administered to 250 from 20 to 60 years. The report examines the potential of the green marketing by investigating customer behavior. This study focuses on the green products as they are the upcoming in India and more likely to establish a standard business model. It shows that customers are willing to express their concern for social and environmental issues through their shopping habits. It is observed that all the independent variables viz, consumer awareness, perception and environmental concerns has no impact on green marketing products. To finish, consumers need to be aware that they are fully part of the market, therefore confronted with the same threats and opportunities in the market like manufacturers and retailers.